2010
DOI: 10.1152/ajpgi.00471.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 regulates hepatic estrogen and androgen metabolism

Abstract: Cyclin D1 is a cell cycle control protein that plays an important role in regenerating liver and many types of cancer. Previous reports have shown that cyclin D1 can directly enhance estrogen receptor activity and inhibit androgen receptor activity in a ligand-independent manner and thus may play an important role in hormone-responsive malignancies. In this study, we examine a distinct mechanism by which cyclin D1 regulates sex steroid signaling, via altered metabolism of these hormones at the tissue and cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The liver transcriptome analysis suggested that the decreased serum TC was closely associated with the proliferation-related anabolism and cell cycle alteration. Estrogen promotes liver proliferation, and is closely related to the cell cycle alteration in liver (41,21), which establishes the closely association among them. As already reported (41), its inhibition broke the liver proliferation ( Figure 4B), further explaining why letrozole compromised the lipid-lowering effect of SAK-HV ( Figure 5), and verifying its role as a "starter" for liver proliferation.…”
Section: Firstmentioning
confidence: 65%
See 2 more Smart Citations
“…The liver transcriptome analysis suggested that the decreased serum TC was closely associated with the proliferation-related anabolism and cell cycle alteration. Estrogen promotes liver proliferation, and is closely related to the cell cycle alteration in liver (41,21), which establishes the closely association among them. As already reported (41), its inhibition broke the liver proliferation ( Figure 4B), further explaining why letrozole compromised the lipid-lowering effect of SAK-HV ( Figure 5), and verifying its role as a "starter" for liver proliferation.…”
Section: Firstmentioning
confidence: 65%
“…Female hormone synthesis is involved in liver proliferation (21). SAK-HV promoted the synthesis of progesterone and estrogen in liver (Figure 3, D-F), which was significantly blocked by PGC-1α knockdown ( Figure 6, B-D).…”
Section: Firstmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggest that male gonadal dysfunction may induce obesity with hyperlipidemia and hyperglycemia by affecting hepatic gluconeogenesis. Therefore, we analyzed the expression of major urinary protein 1 (MUP1), which is a typical androgen-responsive gene in mouse liver, 22,23) to confirm that the surgical castration had attenuated androgen activity in the liver. The level of MUP1 in the livers of Cast mice was significantly decreased compared with that in Sham mice (p<0.01; Fig.…”
Section: Body Weight Food Intake and Tissue Weightmentioning
confidence: 99%
“…Previous reports have shown that cyclin D1 can directly enhance estrogen receptor activity and inhibit androgen receptor activity in a ligand-independent manner. Indeed, hepatic expression of cyclin D1 leads to increased serum estradiol levels, increased estrogen-responsive gene expression, and decreased androgen-responsive gene expression in regenerating liver (Mullany et al, 2010). The "black" module containing 91 genes shows enrichment in tight junction assembly and cell cycle regulation.…”
Section: Pathway-enrichment Analysismentioning
confidence: 99%